PROOF OF MATHEMATICAL FORMULAS USING THE METHOD OF MATHEMATICAL INDUCTION - Sobirova Dinora Umidjon qizi (TADQIQOTLAR, 2025)
Abstract:  Mathematical  induction  is  a  fundamental  method  of  proof  in mathematics, particularly useful in establishing the validity of formulas and statements involving natural numbers. This article explores the principles and logical structure of mathematical induction through carefully selected examples and step-by-step analyses. By  applying  this  method  to  various  arithmetic  and  algebraic  formulas,  the  study demonstrates  how  induction  provides  a  clear  and  rigorous  approach  to  proof construction.